Contribution to low-carbon cement studies: Effects of silica fume, fly ash, sugarcane bagasse ash and acai stone ash incorporation in quaternary blended limestone-calcined clay cement concretes - Tino Balestra, Carlos Eduardo; Garcez, Lilyanne Rocha [UNESP]; Couto da Silva, Leandro; Veit, Márcia Teresinha; Jubanski, Eliziane; Nakano, Alberto Yoshihiro; Pietrobelli, Marina Helena; Schneider, Ricardo; Ramirez Gil, Miguel Angel [UNESP] (Elsevier, 2023)
Nearly 10% of global carbon dioxide (CO2) emissions come from Portland cement production, in turn exacerbating the Greenhouse Effect. Consequently, the development of alternative materials to mitigate this adverse environmental impact is essential. Limestone-Calcined Clay Cement (LC³) is presented in academic literature as an alternative for reducing CO2 levels from the cement industry without significant modifications in concrete properties. However, the use of wastes from other industries – known as supplementary cementitious materials (SCMs) – in LC³ mixtures should be investigated due to the interaction between SCMs and calcined clays. This study evaluated the properties of Limestone-Calcined Clay Cement Concretes containing different SCMs, namely silica fume, fly ash, sugarcane bagasse ash and acai stone ash, in fresh and hardened states, as well as its durability. Slump, compressive and splitting tests, carbonation and volumetric electrical resistivity analyses, Thermogravimetric Analysis (TGA), Energy Dispersive X-Ray Spectroscopy (EDS), X-Ray Fluorescence (XRF) and Scanning Electron Microscopy (SEM) images were performed in this study. Results showed that high superplasticizer dosages are required in LC³ in order to obtain workable concretes independent of SCMs presence. A competition between SCMs and calcined clay for the portlandite consumption in pozzolanic reactions was noted, reducing compressive strength between 20% and 45% of LC³ mixtures. TGA analysis showed that all portlandite was consumed, mainly by the pozzolanic reactions from calcined clay. The presence of SCM in LC³ concretes increased the electrical resistivity up to 48%. However, all LC³ concretes presented higher carbonation fronts compared to the reference Portland cement concrete due to the low availability of calcium to react with CO2 that penetrates through concrete pores. Among the SCMs, silica fume, fly ash and sugarcane bagasse ash presented a suitable performance to use in LC³ mixture. However, LC³ silica fume concretes presented the best global performance considering concrete properties in fresh and hardened state, as well as its durability.
Keywords: Carbon dioxide; Concrete; Green house effects; Limestone-calcined clay cements; Supplementary cementitious materials